The Role of Accounting Digitization in Entrepreneurial Success in West Java : Quantitative Study of Efficiency, Accuracy, Cost Reduction, Customer Satisfaction, and Data Security - Eka Merdekawati Imeda Seseli; Kathleen Asyera Risakotta; Adhi Bawono (Eastasouth Institute, 2023)
The aim of this study was to investigate the role of accounting digitization in entrepreneurial success in West Java. A quantitative research approach was used, and data were collected from 250 small and medium-sized enterprises (SMEs) using a structured questionnaire. The study analyzed the impact of accounting digitization on efficiency, accuracy, cost reduction, customer satisfaction, and data security using Structural Equation Modeling (SEM) with Smart PLS software. The results of the study showed that accounting digitization has a significant positive impact on all five constructs. Specifically, the use of accounting digitization tools improves the efficiency and accuracy of accounting processes, leading to cost savings and increased customer satisfaction. Additionally, data security measures are crucial to protect sensitive financial information. The study highlights the importance of government support and policies that encourage the adoption of accounting digitization by SMEs in West Java. This can help SMEs to remain competitive in the global market, increase productivity, and create more job opportunities. However, the study has some limitations, such as the focus on only one region and the use of a quantitative research approach. Future research can use a qualitative research approach to gain more in-depth insights into the experiences and perceptions of SME owners and managers regarding accounting digitization.